Hoff Bifurcation Analysis on Nonlinear Dynamical Systems - Tee Loong Soon (Universiti Malaysia Terengganu, 2023)
Dynamical systems have been very prominent for their various functions in real life, for instance in the population growth model. There have been many researched systems such as the Liu system, Chen system, Lu system, Qi system and Zhou system that have been studied intensively. Our main research here is on a modified Lorenz system.